Influence of emotions on consumer buying behavior - Soodan, Vishal; Chandra Pandey, Akhilesh (Journal of Entrepreneurship, Business and Economics, 2016)
Consumer behavior is always uncertain and rational. The complex black box of consumer is a chal-lenge to the marketers and researchers across the world for its nature and tendency to change within no time. Consumer responses towards different marketing programs cannot be same and hence differ by means of its actions which are emotional and always stated as irrational. There are different emo-tional chords of consumers targeted by marketers in order to generate sales and managing effectively the marketing program. Present study is an attempt to investigate the role of emotions on FMCG pur-chases. The study highlighted the relevant emotions in consumer purchases of FMCG products with the help of factor analysis and was conducted in north India to serve the purpose of analyzing the role of emotions in FMCG purchases. Research paper Reference to this paper should be made as follows: Soodan, V., Pandey, A. C.(2016). “Influence of emotions on consumer buying behavior: A study on FMCG purchases in Uttarakhand, India”, Journal of Entrepreneurship, Business and Economics, Vol. 4, No. 2, pp. 163–181